The effect of maternal age at first birth on vocabulary and social and emotional outcomes for Aboriginal and Torres Strait Islander children - Skelton, F (Department of Social Services, 2015)
This article uses Footprints in Time to examine the contribution fathers make to health outcomes for Indigenous children.
Footprints in Time: The Longitudinal Study of Indigenous Children: Report from Wave 5
Keywords: Families -- Fathers; Families -- Parents and Parenting; Children -- Indigenous; Families and relationships; Children; Families; Indigenous; Fathers; Parents and Parenting; Families and relationships